PENGEMBANGAN BAHAN AJAR GEOMETRI DALAM PERMAINAN LATO-LATO - Jefri Saldi; Lutfiyah Lutfiyah; Aswar Anas (IKIP Budi Utomo, 2023)
This study aim to produce teaching materials for geometry modules in lato-lato games to understand the material of lines and angles in terms of validity, practicality and effectiveness. This type of research is Research and Development (R&D), using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The results showed that the media expert's validation score obtained a score of 83.3% from validator 1 and 81.6% from validator 2, both of which indicated very valid categories. The material expert validation score obtained a score of 83.3% from validator 1 and 80% from validator 2, both of which indicated very valid categories. The validity value was also obtained from a small-scale trial, namely the student response questionnaire which obtained a score of 86.4% in the very valid category and the mathematics teacher's response questionnaire obtained a score of 91.2% in the very valid category. While the practicality score obtained a score of 86.5% from the student response questionnaire, 87.5% from the teacher response questionnaire and 94% from the module implementation observation sheet, all three of which were included in the very practical category. The value of effectiveness is obtained from the results of student tests. Student test scores after using the module during learning get a percentage score of 80% which states that it is classically complete. Thus, the module has fulfilled the aspects of validity, practicality and effectiveness and can be used in the learning process.